دور إدارة المعرفة في تعزيز أداء المؤسسة - بن سهوة, نذير; مكيد, علي (جامعة الوادي - University of Eloued, 2014)
شهد العالم في العقود الأخيرة تطورات هائلة في مختلف المجالات، ومن أبرز هذه التطورات التحول نحو اقتصاد المعرفة، هذا الاقتصاد الذي أضحت فيه المعرفة عاملا أساسيا في توليد الثروة وتحقيق الرفاهية على المستوى العالمي، حيث أصبحت المعرفة موردا أساسيا في عمليات الإنتاج يفوق أهمية الموارد المادية الأخرى، ومع هذا التطور الذي حدث على مستوى الاقتصاد العالمي كان لابد أن يصاحبه تطور مماثل على مستوى الإدارة والفكر الإداري. من هنا ظهر أسلوب إدارة المعرفة في العقود الأخيرة والذي يعد من أهم وأنجع الأساليب الإدارية، والذي يعنى بالاستغلال الأمثل للمعرفة الضمنية والصريحة في المؤسسة بهدف تحسين أداءها كميزة تنافسية تمكنها من التفوق والتميز على منافسيها، وتعتمد إدارة المعرفة في ذلك على دعامتين رئيسيتين هما، أولا الأفراد ذوي الخبرة والكفاءة أو ما يعرف بعمال المعرفة، وثانيا نظم المعلومات وتكنولوجيا المعلومات والتي تجد فيهم إدارة المعرفة وسائل فعالة لتحقيق أهدافها. In recent years, the world has made considerable progress in all areas, and among these spectacular advances has been the transition to a thrifty economy, that economy whose knowledge has become an essential criterion in the creation of wealth and the achievement of prosperity in the world. international level in such a way that knowledge has become a major source of productive action beyond the importance of other material resources, and with this progress made at the international economic level it is essential that progress becomes representative in the administration and administrative thinking. From there appeared an administrative mode of knowledge during the last decades is becoming besides one of the most important and powerful of the administrative process constituting an exemplary exploitation of the implicit and explicit knowledge within the organization to improve performance of the company as a competitive advantage allowing it to distinguish itself from its competitors, knowledge management relies in this sense on two important pillars: the first for individuals with the experience and recognized competence in knowledge management. And the second: information systems and technologies in which knowledge management finds effective ways to achieve its objectives.
مقال
Keywords: إدارة المعرفة، اقتصاد المعرفة، تحسين الاداء; Knowledge Management, Knowledge Economy, Performance Improvement